VA Mycorrhizal Association in Weeds of Seminatural Grassland of Sagar - Vyas, Deepak; Singh, Pradeep Kumar; Mishra, Mahendra Kumar; Dubey, Archana (Indian Journal of Agroforestry, 2020)
In the present investigation 33 plant weeds belonging to 20 families were surveyed for their mycorrhizal association. The result revealed that Parthenium hysterophorusÂ of Asteraceae family colonized 72.40% Â± 0.50 of the roots whereas Sporobolus indicus of Poaceae family had minimum root colonization 8.00% Â± 2.22. The result also suggested that the percent root colonization varied among the plant weeds irrespective of their families. Roots of 30% plant weeds showed arbuscules and vesicles, 12% plants showed only arbuscules, 27% plants showed only vesicles and 31% plants show only mycelial structure. Arum-type arbuscules dominanted among the test plant weeds. Result also indicated that Parthenium hysterophorus could be used as a natural source of mass cultivation of VAM fungi.